PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN HERBAL SKINCARE - Amara Suryani Putri; Budi Istiyanto (JOURNAL SCIENTIFIC OF MANDALIKA (JSM), 2022)
This study was conducted to determine the effect of service quality, product quality, and price on customer satisfaction with Herbal SR12 skin care products, either individually or in combination. Men and women who had used SR12 products were participants in this study. By using the Lemeshow formula and purposive sampling approach, a sample of 96 people was used. The descriptive statistics and multiple regression analysis performed in SPSS 21 provide the basis for the analysis. The findings of this study indicate that product quality has a negative impact on the level of customer satisfaction SR12, but the service quality variable has no significant effect and the price level variable has no significant effect on customer satisfaction SR12.